The Role of Shopping Malls on Kurdistan Regional Government’s Economy - Ali, Bayad Jamal; Gardi, Bayar; Othman, Baban Jabbar; Sabir, Bawan Yassin; Sorguli, Sarhang; Burhan Ismael, Nechirwan; Hamza, Pshdar Abdalla; Aziz, Hassan Mahmood; Ahmed, Shahla Ali; Anwar, Govand (International Journal of Humanities and Education Development (IJHED), 2021)
This research covers the history of shopping malls in KRG and how the malls were a new shopping destination for the citizens of KRG. However, with the current economic crisis in KRG and the financial difficulties that people have been facing in the past two years. This research studies the impact of economy crisis on the spending's of individuals and the shopping centers that were used to be filled with people who would spend a huge amount of money on shopping. We distributed 240 questionnaires in three languages: Kurdish, Arabic and English in order to identify people’s shopping behavior and the factors that attract people to the shopping malls. The things that we managed to accomplish in this research was that people are pessimistic about the financial situation and future of the economy. People would rather save their cash than spending it on shopping. These achievements met the main objective of this study which was to find out people’s behavior to do their shopping and satisfy their needs and wants that are provided in the malls.